Antecedents Of Safe Use Of Hospital Information Systems Based On Sociotechnical Perspective - Salahuddin, Lizawati (UTeM, 2016)
Hospital Information System (HIS) could potentially improve the quality of healthcare services and patient safety. Nevertheless, there is a number of growing evidence that show HIS can pose risk to patient safety when it is poorly designed, implemented, or adopted. Most of the preventive solutions have been focusing on improving the software design. Conversely, patient safety is not merely dependent upon HIS, but also influenced by its interactions with users, other technologies, and environment. Therefore, this research proposes a conceptual model for a safe use of HIS by considering the sociotechnical aspect. Exploratory mixed methods methodology was employed. The first phase involved qualitative exploration of the safe use of HIS and its antecedents. Interview transcripts from 31 medical doctors at three Malaysian government hospitals implementing Total Hospital Information System (THIS) were collected. A quantitative data collection followed as the second phase to evaluate the research model. A total of 450 medical doctors from the three hospitals participated in the questionnaire survey. Structural Equation Modelling (SEM) was used for quantitative data analysis. The findings showed that knowledge, system quality, and team work has a significant direct effect on vigilance, while task stressor has a significant direct effect on procedure compliance. Teamwork emerged as the most important factor in determining the safe use of HIS. In addition, vigilance has a significant direct effect on both patient safety and patient care quality, whereas procedure compliance has significant direct effect on patient safety. Besides that, vigilance mediates the effect of knowledge, system quality, and teamwork on patient care quality. Procedure compliance mediates the effect of task stressor on patient safety. The model has portrayed predictive capability and predictive relevance, implying that the model could effectively explain the safe use of HIS and its outcomes. Hence, this research concludes that healthcare organisations and practitioners should give attention to the sociotechnical aspect of the safe use of HIS antecedents in reducing error, as well as increasing the quality of patient care.